New law and ethics in mental health advance directives : the Convention on the Rights of Persons with Disabilities and the right to choose - Weller, Penelope (East Sussex [UK] : Routledge, 2013)
'The recognition of positive rights and the growing impact of human rights principles has recently orchestrated a number of reforms in mental health law, bringing increasing entitlement to an array of health services. In this book, Penelope Weller considers the relationship between human rights and mental health law, and the changing attitudes which have led to the recognition of a right to demand treatment internationally. Weller discusses the ability of those with mental health problems to use advance directives to make a choice about what treatment they receive in the future, should they still be unable to decide for themselves. Focusing on new perspectives offered by the Conventions on the Rights of Persons with Disabilities (CRPD), Weller explores mental health law from a variety of international perspectives including: Canada, Australia, New Zealand and the United Kingdom, where policies differ depending on whether you are in England and Wales, or Scotland. These case studies indicate how human rights perspectives are shifting mental health law from a constricted focus upon treatment refusal, towards a recognition of positive rights. The book covers topics including: refusing treatment new approaches in human rights international perspectives in mental health law the right to demand treatment. The text will appeal to legal and mental health professionals as well as academics studying mental health law, and policy makers'--
Includes bibliographical references (p. [162]-176) and index.
Keywords: Convention on the Rights of Persons with Disabilities and Optional Protocol -- (2007).; Mental health laws; Mental health -- Moral and ethical aspects; Insanity (Law).; Mental illness -- Psychological aspects